On one problem with non-local boundary conditions - Čiegis, Raimondas; Štikonienė, Olga; Suboč, Olga (Lietuvos matematikos rinkinys, 2001)
In this article two problems with non-local boundary conditions are analysed: stationary diffusion problem with constant coeficients and non-local boundary condition, and stationary diffusion problem with additional convection term and non-local boundary condition. Finite difference schemes are constructed and investigated. The sufficient conditions for the existence of an unique solution are obtained.